PELAKSANAAN PERTIMBANGAN TEKNIS PERTANAHAN (PTP) TERKAIT PERSETUJUAN KEGIATAN KESESUAIAN PEMANFAATAN RUANG (PKKPR) DIKANTOR BPN KAB.PROBOLINGGO: PELAKSANAAN PERTIMBANGAN TEKNIS PERTANAHAN (PTP) TERKAIT PERSETUJUAN KEGIATAN KESESUAIAN PEMANFAATAN RUANG (PKKPR) DIKANTOR BPN KAB.PROBOLINGGO - MEIDEZELLA; DWI WAHYUNI; KHOLIDAZIA ELHAMZAH FATHULLAH (JUSTNESS - Jurnal Hukun dan Agama, 2025)
Abstract The risk-based business licensing system operated electronically by the Investment Coordinating Board (BKPM) is known as the Online Single Submission Risk Based Approach (OSS RBA). The implementation of technical considerations for land (PTP) is carried out by the National Land Agency Office, one of the classifications is the suitability of space utilization activities (KKPR) for business activities carried out through KKPR and PKKPR, licensing can be carried out even though the RDTR is not yet available or the existing RDTR has not been integrated into the OSS system, by using the PKKPR mechanism. while those that have been integrated into the OSS system use KKKPR, this manuscript aims to determine the meaning, application requirements, procedures, and obstacles to technical considerations for land in the framework of approval of the suitability of space utilization activities at the ATR/BPN office of Probolinggo Regency. This study adopts an empirical research method with a conceptual approach by conducting interviews as a data collection technique, Against one of the employees of the ATR/BPN office of Probolinggo Regency, The results of this study are the implementation of Technical Considerations for Land related to the Approval of the Suitability of Business Space Utilization Activities running according to the Service Provision Guidelines, The obstacles include the applicant cannot be contacted, differences in the terms and conditions between the OSS system and the requirements for Technical Considerations for Land, lack of communication between the applicant and the ATR/BPN office of Probolinggo Regency. Keywords: Land Technical Considerations, business licensing, space utilization.